Involvement of the Programmed Death 1/Programmed Death Ligand 1 Pathway in the Immune Microenvironment of Chronic Periapical Lesions - Yujin Song; Seohee Park; Hyeseong Jin; Byungyoon Hyun; Kyu-Young Oh (International Dental Journal)
Introduction and aims: This study aimed to determine the pathogenic role and clinicopathological significance of the immune microenvironment including the programmed death 1 (PD-1)/programmed death ligand 1 (PD-L1) pathway in chronic periapical lesions. Methods: A total of 20 chronic periapical lesions consisting of 10 periapical granulomas and 10 periapical cysts were included in this study. Immunohistochemistry was performed for immune cell populations, including PD-L1, PD-1, CD4, CD8, FOXP3, and CD20. Immune cell populations were quantitatively evaluated on digitized slides. The associations between each immune cell population and clinicopathological factors and between immune cell populations were statistically analysed. Results: Lesion size was positively associated with the density of PD-L1+ macrophages (P < .001, Fisher exact test; r = 0.455, P = .044, Pearson correlation analysis) and CD8+ cytotoxic T cells (P = .020, Fisher exact test; r = 0.471, P = .036, Pearson correlation analysis). No associations were found between immune cell populations and other clinicopathological factors, including age, sex, lesion location, and diagnosis. A moderate positive correlation was observed between the density of PD-L1+ macrophages and CD8+ cytotoxic T cells (r = 0.537, P = .015). The density of PD-1+ cells showed a strong positive correlation with the density of CD4+ helper T cells (r = 0.719, P < .001) and FOXP3+ regulatory T cells (r = 0.784, P < .001). Conclusion: These findings suggest that cytotoxic T cells are implicated in the progression of chronic periapical lesions, which may be regulated by PD-L1+ macrophages. PD-1 may be involved in helper T cell exhaustion and regulatory T cell activity in chronic periapical lesions. Clinical relevance: We demonstrated the involvement of PD-L1 and PD-1 in the regulation of T cell immunity in chronic periapical lesions. These findings suggest that activating the PD-1/PD-L1 pathway is a potential therapeutic strategy for chronic periapical lesions.